The Stand Of Electronic Evidence In Cyber Crime Law Enforcement In Indonesia - Dewic Sri Ratnaning Dhumillah (Green Publisher Indonesia, 2024)
Crime in the cyber world certainly has a significant impact. People think that Indonesia has a Criminal Code that cannot cover crimes in cyberspace, which is a new crime. This is what makes the government have to issue regulations regarding cyber crime or cyber crime. With regard to enforcing cybercrime law, of course, a regulation is needed in positive law. It also regulates the punishment and how the evidence for cyber crimes and the position of electronic evidence are. This research method uses the normative method. The existence of electronic evidence in proving cybercrime has been alluded to in Law Number 19 of 2016 concerning Amendments to Law Number 11 of 2008 concerning Information and Electronic Transactions. In Article 5 of Law Number 11 of 2008, it explicitly mandates that